2018
DOI: 10.1186/s12864-018-4809-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals phylogenetic distribution patterns of secondary metabolites in Amycolatopsis species

Abstract: BackgroundGenome mining tools have enabled us to predict biosynthetic gene clusters that might encode compounds with valuable functions for industrial and medical applications. With the continuously increasing number of genomes sequenced, we are confronted with an overwhelming number of predicted clusters. In order to guide the effective prioritization of biosynthetic gene clusters towards finding the most promising compounds, knowledge about diversity, phylogenetic relationships and distribution patterns of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
107
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 78 publications
15
107
1
Order By: Relevance
“…We showed that BGCs and CGCs in Streptomyces are highly diverse and exhibit variable patterns of phylogenetic distribution, with hybrid BGCs and inter-strain variation further expanding the BGC repertoire present in any one genome. These findings are consistent with recent reports in other genera of Actinobacteria 6,18,19 and also highlight the power of mining the genomes of closely related strains. In a recent study of ten Streptomyces strains with 16S rRNA gene sequences that are all identical to the type strain of Streptomyces cyaneofuscatus and hence are considered the same species, no two strains appear to exhibit identical secondary metabolomic profiles 32 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We showed that BGCs and CGCs in Streptomyces are highly diverse and exhibit variable patterns of phylogenetic distribution, with hybrid BGCs and inter-strain variation further expanding the BGC repertoire present in any one genome. These findings are consistent with recent reports in other genera of Actinobacteria 6,18,19 and also highlight the power of mining the genomes of closely related strains. In a recent study of ten Streptomyces strains with 16S rRNA gene sequences that are all identical to the type strain of Streptomyces cyaneofuscatus and hence are considered the same species, no two strains appear to exhibit identical secondary metabolomic profiles 32 .…”
Section: Discussionsupporting
confidence: 92%
“…We characterized the biosynthetic diversity in 1,110 Streptomyces genomes using antiSMASH 17 (Supplementary Table S1). We detected a total of 34 major classes of BGCs, which is consistent with previous reports in other Actinobacteria genera such as Salinispora and Amycolatopsis 6,18,19 . , Streptomyces thermoautotrophicus H1 (n = 9 BGCs) and S. thermoautotrophicus UBT1 (n = 11 BGCs).…”
Section: Widespread Distribution and Diversity Of Bgcs In Streptomycessupporting
confidence: 91%
“…Recent comparative genomics of the genus Amycolatopsis, a large, widely distributed genus well-known as a source of bioactive metabolites, illustrates the power of this strategy. The pan-genome of members of this genus comprises a small core genome largely involved with translation and ribosome biogenesis and a 'huge' accessory genome that includes numerous genes encoding biosynthesis of specialized metabolites [55]. Phylogenetic analysis of the genus revealed four distinct lineages that correlated perfectly in their capacities to produce specialized metabolites; moreover, the extensive diversity of BGCs revealed that the majority were unique to Amycolatopsis.…”
Section: Is Biogeography a Roadmap To Drug Discovery?mentioning
confidence: 99%
“…In light of these developments, it clearly makes good sense to focus bioprospecting campaigns on micro‐organisms with moderate to large genomes. Another important development is the realization that in some actinobacterial taxa, such as the genera Amycolatopsis , Frankia and Micromonospora , there is a link between the distribution of NP‐BGCs and phylogeny (Adamek et al ; Carro et al ; Nouioui et al ). In addition, information drawn from whole‐genome sequences is providing fascinating insights into how micro‐organisms adapt to extreme habitats, as witnessed by the ability of members of the actinobacterial family Geodermatophilaceae to withstand extreme environmental conditions that prevail in hyperarid desert habitats (Castro et al , b).…”
Section: Introductionmentioning
confidence: 99%